2011
DOI: 10.1007/s10689-011-9450-1
|View full text |Cite
|
Sign up to set email alerts
|

The liver: another organ involved in Muir Torre syndrome?

Abstract: Muir Torre syndrome is a rare autosomal dominant cancer-predisposing syndrome characterized by the occurrence of sebaceous gland neoplasms and/or keratoacanthomas associated with visceral malignancies that belong to the spectrum of hereditary non polyposis colorectal cancer (HNPCC), i.e., tumors of gastrointestinal and genitourinary tracts. Hepatobiliary malignancy in association with Muir Torre syndrome has rarely been reported. Here, we describe a case of Muir Torre syndrome associated with an hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Based on this high prevalence of MMR-deficiency and the assumption that tumors with MMR-deficiency were caused by the underlying germline mutation (and a somatic mutation as the second hit), we estimated the RR of MMR-deficient prostate cancer for all mutation carriers combined and for MSH2 mutation carriers alone to be 3.2 (95 % CI 2.0–6.3) and 5.8 (95 % CI 2.6–20.9), respectively, providing further support for the inclusion of prostate cancer as part of the Lynch syndrome-associated tumor spectrum. However, the issue of whether prostate cancer risk is increased for men with Lynch syndrome is still debatable as other studies have not found evidence for an increased risk [31, 32]. Therefore, future studies using large prospective studies of known mutation carriers with long follow-up will be needed to conclusively resolve the issue of risk of prostate cancer for MMR gene mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this high prevalence of MMR-deficiency and the assumption that tumors with MMR-deficiency were caused by the underlying germline mutation (and a somatic mutation as the second hit), we estimated the RR of MMR-deficient prostate cancer for all mutation carriers combined and for MSH2 mutation carriers alone to be 3.2 (95 % CI 2.0–6.3) and 5.8 (95 % CI 2.6–20.9), respectively, providing further support for the inclusion of prostate cancer as part of the Lynch syndrome-associated tumor spectrum. However, the issue of whether prostate cancer risk is increased for men with Lynch syndrome is still debatable as other studies have not found evidence for an increased risk [31, 32]. Therefore, future studies using large prospective studies of known mutation carriers with long follow-up will be needed to conclusively resolve the issue of risk of prostate cancer for MMR gene mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of MSH2 expression in the HCC as well as the MSI-H phenotype in the histopathological absence of significant chronic liver disease argues against the presence of coincidental sporadic HCC. Recently, Morando et al [25] reported a patient with Muir-Torre syndrome and HCC in the presence of alcoholic liver disease and fibrosis. Since they did not provide MSI analysis or MMR-IHC, a coincidence cannot be excluded in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with SC may be at increased risk for developing other forms of cancer, either preceding or following a diagnosis of SC,4 primarily related to SC's association with Muir-Torre syndrome, an autosomal dominant syndrome within the spectrum of hereditary nonpolyposis colorectal cancer. 9 SC has been reported to have a rate of distant metastasis in the range of 8 to 29% and a 5-year mortality rate in the range of 4 to 20%.5-7,10 Thus, it is imperative that cases of SC be treated aggressively. There is mounting evidence that the preferred method of treatment of SC is by Mohs micrographic surgery (MMS).…”
mentioning
confidence: 99%